Verrucous papillary lesions: dilemmas in diagnosis and terminology - Kallarakkal, T.G.; Ramanathan, A.; Zain, R.B. (2013)
Verrucous papillary lesions (VPLs) of oral cavity are diagnostically challenging as they include a spectrum of benign, potentially malignant, and frankly malignant lesions. A majority of the benign VPLs have viral aetiology and include commonly occurring squamous papilloma along with verruca vulgaris, focal epithelial hyperplasia, and condyloma. Current understanding of potentially malignant VPLs is perplexing and is primarily attributed to the use of confusing and unsatisfactory terminology. Clinically and histologically oral verrucous hyperplasia, a potentially malignant disorder, resembles oral verrucous carcinoma and may be indistinguishable from one another. The most reliable way to separate these entities on routine haematoxylin-eosin stained tissue sections is to recognize the exophytic growth patterns of oral verrucous hyperplasia from the combined exophytic and endophytic growth patterns associated with verrucous carcinoma. A review of the literature showed that there is a lot of confusion regarding the current clinical and histopathological guidelines to diagnose this potentially malignant entity. The criteria elaborated by different authors in establishing the diagnosis of oral verrucous hyperplasia are discussed in detail. A brief overview of the treatment modalities adopted is also discussed. The need for establishing a clear understanding of this potentially malignant entity is stressed as it may have far reaching implications on its management.